Deep eutectic solvents improve the stability of forsythoside A. Issue 4 (13th May 2021) - Zhang, Qin; Dong, Zhe; Du, Huizhi
Abstract: Forsythoside A is used as the main chemical marker for quality control of Forsythia suspensa (Thunb.) Vahl ( F. suspensa, Lianqiao in Chinese) fruits and leaves. The hydrolysis of forsythoside A at high temperature and effects of deep eutectic solvents (DESs) on stability of forsythoside A were studied in the article. Forsythoside A, I, and H may be directly converted into each other at high temperature. With more heating time, they are gradually decomposed into smaller molecular compounds. High temperature, alkaline conditions, high humidity, the oxidant, and light drastically destroyed stability of forsythoside A, while acidic conditions and the antioxidant protected it. Compared with water and alcohol solvents, DESs improved effectively stability of forsythoside A due to the formation of hydrogen bonds between DESs and forsythoside A. Our research preliminarily uncovered the converting mechanism of forsythoside A and confirmed that DES improved the stability of forsythoside A. Abstract :